Huge [large type] - Fuerst, James W. (James William) (Thorndike Press large print core, 2009)
Twelve-year-old Eugene "Huge" Smalls is short, mean, angry, and brilliant, characteristics which win him no friends, but he is also an amateur sleuth with his first real case, which leads him to believe life might be better if he did not imagine himself a character in a Raymond Chandler novel.